Evaluating a Japanese Character-Based Teaching Program in Early Childhood Education: A Study in Gorontalo City - Pade, Reza Bakhrun Fidianto; Sudiyatno, Sudiyatno; Pusporini, Widowati (Universitas Negeri Makassar, 2025)
This study aims to evaluate the effectiveness of a Japanese teaching program implemented in Gorontalo City, Indonesia, in fostering character development in early childhood education. Using the discrepancy evaluation model and a mixed-methods approach, this study involved 20 children, 6 parents, 7 teachers, and 3 administrative personnel at Sakura Kids Preschool and Day Care. Data were collected through observation, interviews, and document analysis. Quantitative data were derived from structured observations on students using a character development rubric and were analyzed using descriptive statistics. Qualitative data from semi-structured interviews with teachers, parents, and administrators supported the quantitative findings and provided deeper insight into implementation practices and cultural adaptation. Results indicate that most children demonstrated good to excellent development in independence, discipline, and responsibility, and social interaction. This study provides concrete recommendations for integrating culturally adapted, specifically Japanese-character-based teaching programs into Indonesia’s early childhood education system, emphasizing the importance of contextualization, consistency, and collaboration among stakeholders.